Synthesis of silicate-bridged ZnO/g-C3N4 nanocomposites as efficient photocatalysts and its mechanism1. Issue 47 (27th May 2015) - Liu, Chong; Li, Chengming; Fu, Xuedong; Raziq, Fazal; Qu, Yang; Jing, Liqiang
<x xml:space="preserve">Abstract</x> The built silicate bridges are favorable for charge transfer and separation, which lead to the greatly enhanced photoactivities of ZnO/g-C3N4.